A review of the genus Bullanga Navás, 1917 (Neuroptera: Myrmeleontidae) - Zhan, Qingbin; Wang, Xinli (Zootaxa, 2014)
A review of genus Bullanga Navás, 1917 is presented. All three species of Bullanga are redescribed and illustrated in detail. The female of Bullanga florida is described for the first time. A key to Bullanga species is also provided.